2015
DOI: 10.1055/s-0034-1392222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EUS-guided tissue acquisition using two different 19-gauge core biopsy needles: a multicenter, prospective, randomized, and blinded study

Abstract: Background and study aims: The optimal core biopsy needle for endoscopic ultrasound (EUS) is unknown. The principle aim of this study is to compare outcomes of EUS-fine-needle biopsy (EUS-FNB) with a new 19-gauge EUS histology needle (ProCore, Cook Medical Inc., Winston-Salem, North Carolina, United States) to a conventional 19-gauge Tru-Cut biopsy (EUS-TCB) needle (19G, Quick-Core, Cook Medical Inc.). Patients and methods: Patients referred for EUS who require possible histologic biopsy were prospectively ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…Comparing the 19G FNA to 22G core, the 22G had higher rates of tissue fragmentation which lead to lower tissue adequacy rates compared to 19G FNA [18]. Dewitt et al compared two 19G core needles in 85 patients and demonstrated superior ability of FNB compared to Tru-Cut biopsy needle in terms of prevalence of diagnostic histology, TSL, and CPT [20]. In a recent study by Hasan MK et al, efficacy and safety of 22-G EUS-FNB for performing EUS-MLB was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the 19G FNA to 22G core, the 22G had higher rates of tissue fragmentation which lead to lower tissue adequacy rates compared to 19G FNA [18]. Dewitt et al compared two 19G core needles in 85 patients and demonstrated superior ability of FNB compared to Tru-Cut biopsy needle in terms of prevalence of diagnostic histology, TSL, and CPT [20]. In a recent study by Hasan MK et al, efficacy and safety of 22-G EUS-FNB for performing EUS-MLB was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be superior to the Tru-cut needle in one multicenter randomized trial. 11 The Sharkcore needle (Sharkcore;…”
Section: Discussionmentioning
confidence: 99%
“…An important question is how well these results might translate into clinical settings. ATM mutations can be detected in fine needle aspirate samples, and loss of tumoral ATM expression could be obtained in fine needle biopsies of pancreatic cancer tumor masses 36,37 and so it would be attractive to test the hypothesis that ATMmutated or otherwise ATM-deficient pancreatic cancers are more sensitive to radiotherapy than ATM-wild-type cancers and if this is the case whether or not the use of radiotherapy for local disease control should take into account the results of tumor molecular profiling. 38,39 Interestingly, we did not find any significant differences in the chemosensitivity of ATM-deficient compared to ATM-intact pancreatic cancer cells with intact ATM even for the Parp inhibitor, olaparib.…”
Section: Discussionmentioning
confidence: 99%